How Zen became Zen the dispute over enlightenment and the formation of Chan Buddhism in Song-dynasty China - Schlütter, Morten (Univ. of Hawai'i Press, 2008)
Morten Schlütter takes a novel approach to understanding one of the most crucial developments in Zen Buddhism: the dispute over the nature of enlightenment that erupted within the Chinese Chan (Zen) school in the 12th century.
Includes bibliographical references (p. 251-275) and index
Chan Buddhism in the Song: some background -- The Chan school and the Song state -- Procreation and patronage in the Song Chan school -- A new Chan tradition: the reinvention of the Caodong lineage in the Song -- A dog has no Buddha-nature: Kanhua Chan and Dahui Zonggao's attacks on silent illumination -- The Caodong tradition as the target of attacks by the Linji tradition -- Silent illumination and the Caodong tradition
Keywords: Geschichte 1050-1150; Zen Buddhism / China / History; Geschichte; Zen Buddhism -- China -- History; Zen-Buddhismus; Songdynastie -- 960-1279; China